PEMODELAN MATEMATIK PERUBAHAN PARAMETER MUTU KERUPUK SELAMA PENGGORENGAN DENGAN PASIR [Mathematical Modeling of Quality Parameter Changes of Chips During Sand Frying] - Siswantoro - -; Budi - Rahardjo; Nursigit - Bintoro; Pudji - Hastuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Chip is a preferred food by all economic levels of society. Before consumption, chip is prepared by frying. There are different kinds of frying methods; one of them is conducted using sand as the heat transfer medium, known as “hot sand frying